2014
DOI: 10.1007/s00467-014-2829-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of early urinary renal injury markers in obese children

Abstract: This study shows that urinary NAG and KIM-1 could be used as a screening method for detection of early renal damage in obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 35 publications
7
61
1
1
Order By: Relevance
“…In addition, these authors reported that a change in BMI over the 6 years of the study, but not the baseline BMI itself, was associated with microalbuminuria, indicating that the growth in body mass may occur faster than the kidneys can adapt [13]. Microalbuminuria was not found to be different between obese children and healthy controls in the study of Goknar et al [11].…”
Section: Microalbuminuriamentioning
confidence: 86%
See 4 more Smart Citations
“…In addition, these authors reported that a change in BMI over the 6 years of the study, but not the baseline BMI itself, was associated with microalbuminuria, indicating that the growth in body mass may occur faster than the kidneys can adapt [13]. Microalbuminuria was not found to be different between obese children and healthy controls in the study of Goknar et al [11].…”
Section: Microalbuminuriamentioning
confidence: 86%
“…Furthermore, urine NGAL can be used as an early biomarker of diabetic nephropathy [16]. However, urine NGAL was not found to be different between obese children and healthy controls in Goknar et al's study [11].…”
Section: Microalbuminuriamentioning
confidence: 90%
See 3 more Smart Citations